2018
DOI: 10.1590/1678-98652018000100001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and glycemic indexes in type 2 diabetes patients

Abstract: Objective To identify the main dietary patterns in type 2 diabetes patients and study their association with glycemic indexes. Methods This is a cross-sectional study carried out in a diabetes treatment reference institution located in the city of Fortaleza (CE). Two R24h were applied, as well as 12h fast blood glucose tests and anthropometric assessments in 188 diabetic patients. The principal components factor analysis method was applied together with a Varimax orthogonal rotation method to identify dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Even though this was an observational study without a control group, this type of research is essential for analyzing the relationships between lifestyle components (nutrition, physical activity, sleep, stress, smoking status) and metabolic parameters. There are other nutritional studies that did not have a control group and are based on observational research alone [ 81 , 82 ]. These studies had the same design; the researchers identified dietary patterns in patients with type 2 diabetes and also studied their associations with the glycemic index and metabolic syndrome components.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this was an observational study without a control group, this type of research is essential for analyzing the relationships between lifestyle components (nutrition, physical activity, sleep, stress, smoking status) and metabolic parameters. There are other nutritional studies that did not have a control group and are based on observational research alone [ 81 , 82 ]. These studies had the same design; the researchers identified dietary patterns in patients with type 2 diabetes and also studied their associations with the glycemic index and metabolic syndrome components.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The primary nutritional strategy in conventional epidemiology is to investigate nutrients and their association with chronic diseases, including diabetes. [3] Diet is one of the primary risk variables influencing other risk factors. [4][5][6] Food selection and eating habits have a critical role in regulating the course of the disease once diabetes develops.…”
Section: Introductionmentioning
confidence: 99%
“…3 Em uma instituição de referência no tratamento do diabetes que recebe usuários do Sistema Único de Saúde (SUS), observou-se que, entre os padrões alimentares identificados, o "tradicional brasileiro", caracterizado pelo consumo de arroz, feijão, frango e alimentos regionais, apresentou correlação negativa com os níveis glicêmicos. 8 Considerando que a alimentação saudável é um fator de proteção contra doenças crônicas não transmissíveis, entre elas o diabetes tipo 2, que desempenha importante papel no tratamento do diabetes e suas comorbidades (p. ex. hipertensão, obesidade e dislipidemia), este estudo teve como objetivo caracterizar o hábito alimentar de idosos diabéticos e não diabéticos com 65 anos ou mais, residentes nas capitais brasileiras e no Distrito Federal.…”
Section: Introductionunclassified